A Multi-Trip Vehicle Routing Problem with Time Windows for Waste Collection in Bidor Region - Wong, Yeun Yee; Jamaian, Siti Suhana (Enhanced Knowledge in Sciences and Technology, 2022)
The household waste collection would be a huge problem if it is not handled properly, thus an efficient plan for waste collection is needed to maintain a clean environment and comfortable living life. This research aims to study a multi-trip vehicle routing problem with time windows (MTVRP) specifically related to household waste collection in Bidor region. In the raised problem, our objective is to minimize the traversing cost, vehicle cost, and penalty from violating time windows and capacity of the vehicle. Since the vehicle routing problem belongs to the NP-hard problem, efficient simulated annealing (SA) is used to solve the problem with the assist of MATLAB software. The latitude and longitude for the disposal center from Tapah and 15 locations in Bidor region were directly taken from the Global Positioning System (GPS). The total distance of the route obtained was recorded in Euclidean distance. The result was run ten times to determine the best solution for the vehicle routing which used the least total distance with zero violate condition in the solution. The seventh result with the minimum cost RM475.988 is the optimum route solution. The cooling process to obtain the best cost for the vehicle route was followed the property of SA algorithm.